Atrial fibrillation and heart failure with preserved ejection fraction: Insights on a unique clinical phenotype from a nationally-representative United States cohort. (1st September 2018) - Goyal, Parag; Almarzooq, Zaid I.; Cheung, Jim; Kamel, Hooman; Krishnan, Udhay; Feldman, Dmitriy N.; Horn, Evelyn M.; Kim, Luke K.
Abstract: Background: Atrial fibrillation (AF) and heart failure often occur concomitantly, representing a clinical phenotype at high-risk for poor outcomes. Differences in the characteristics, management, and in-hospital outcomes of AF among those with heart failure with preserved ejection fraction (HFpEF) and those with heart failure with reduced ejection fraction (HFrEF) are not well characterized. Methods and results: Using the National Inpatient Sample, we identified hospitalizations in 2008–2012 for HFpEF and for HFrEF, with and without AF based on ICD-9-CM codes. We examined patient characteristics, procedural rates, and in-hospital outcomes. AF was common among both HFpEF and HFrEF, and increased in prevalence over the study period. A very low proportion of the cohort underwent either direct-current cardioversion or catheter-ablation. Compared to those without AF, those with AF experienced higher in-hospital mortality regardless of heart failure subtype. In multivariable regression analysis, AF was associated with in-hospital mortality in HFpEF (OR 1.10, CI [1.08–1.11]), but not in HFrEF (OR 0.93 [0.92–0.94], p-for-interaction < 0.001). Conclusions: Our study revealed that the prevalence and adverse impact of AF on those with HFpEF is substantial, providing a rationale to rigorously investigate strategies, such as rhythm-control, to improve outcomes for this particularly vulnerable subpopulation. Highlights: HFpEF with concurrent AF is common and is becoming increasingly prevalent. Rates of cardioversion and catheter-ablation are very low in both HFpEF and HFrEF. Cardioversion and catheter-ablation are less likely performed in nonwhite patients. AF is associated with in-hospital mortality among those with HFpEF, but not HFrEF.